Prediction Of User Acceptance And Adoption Of Smart Phone For Learning With Technology Acceptance Model - Sek, Yong Wee; Lau, Siong Hoe; Teoh, Kung Keat; Law, Check Yee; Parumo, Shahril (Asian Network for Scientific Information, 2011)
This study examines how the Technology Acceptance Model (TAM) can be used as a practical tool for early user acceptance and adoption of testing mobile communication devices for learning by evaluating the relationships among perceived usefulness, perceived ease of use, attitude towards using, behavioural intentions to use and actual use. In the study, 60 potential users were presented with an introductory demonstration of smart phone for a digital systems course. Following the demonstration, data on user perceptions and attitudes about smart phones were gathered based on this initial exposure. Subjects with prior experience using the smart phones were eliminated from further analysis resulting in a final sample of 40 users. Hierarchical multiple regression was used to assess the overall model and influence of each variable of interest in determining actual use of smart phone. The analysis showed that both the user perceptions and attitudes have significant positive effects on behavioural intention and actual use of smart phone. Implications of these findings for practice and research are examined.